2015
DOI: 10.1016/j.amjmed.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mesenteric Ischemia: A Rare Cause of Chronic Abdominal Pain

Abstract: Chronic mesenteric ischemia may be diagnosed in the presence of a splanchnic syndrome and stenosis of a single splanchnic vessel, typically assessed using computed tomography angiography. In selected patients, endovascular revascularization had similar efficacy as, and lower complication rates than open revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Firstly, his symptoms consisted primarily of diarrhoea and nausea for the majority of his illness, with pain being a very late feature. This is unusual: in one retrospective review of 54 cases of mesenteric ischaemia, pain was present in 98% of patients, with diarrhoea only in 24.5% and nausea in 2% [ 4 ]. The clinicians therefore applied a ‘representativeness heuristic’, wherein the patient exhibited a cluster of symptoms or ‘illness script’ common to those with inflammatory bowel disease, rather than mesenteric ischaemia [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, his symptoms consisted primarily of diarrhoea and nausea for the majority of his illness, with pain being a very late feature. This is unusual: in one retrospective review of 54 cases of mesenteric ischaemia, pain was present in 98% of patients, with diarrhoea only in 24.5% and nausea in 2% [ 4 ]. The clinicians therefore applied a ‘representativeness heuristic’, wherein the patient exhibited a cluster of symptoms or ‘illness script’ common to those with inflammatory bowel disease, rather than mesenteric ischaemia [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also falsely reassuring was the absence of biochemical markers of malnutrition such as anaemia or hypoalbuminaemia; as well as frank lactataemia. However, serum lactate levels are rarely raised in chronic mesenteric ischaemia due to the capacity of the liver to metabolise lactate delivered via the portal vein [ 4 ]. As such, serum lactate is elevated only in cases of critical transmural ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In general, long-term patient survival does not seem to be influenced by the type of revascularization performed [19][20][21] . ET is associated with lower peri-procedural morbidity [22,23] . However, Zacharias et al [24] recently reported a higher 3-year patency rate using OT (OT 91%; ET 74%), and Arya et al [25] also found higher mid-and long-term patency rates for OT, while Cai et al [26] saw significantly higher symptom recurrence within 3 years with ET.…”
Section: Resultsmentioning
confidence: 99%
“…Computed tomography angiography was the key diagnostic tool for 60% of the patients. Endovascular and open surgical revascularization had similar early and late outcomes [13].…”
mentioning
confidence: 87%
“…Vascular reconstruction can be accomplished by Endarterectomy or aortomesenteric bypasses [12] of 54 patients with chronic mesenteric vascular ischemia, 43 patients were treated with endovascular revascularization and 11 patients with open surgical revascularization [13]. The symptoms were abdominal pain in 98% of the patients, weight loss in 53% of the patients, and diarrhea in 25% of the patients.…”
mentioning
confidence: 99%